(untitled) (Altre Modernità, 2011)
The Musée du Quai Branly features ethnological findings from four continents: Africa, Asia, Oceania and the Americas. Today scholars and experts are still debating whether in this particular museum/institution the aesthetic concern should prevail - allowing visitors to relate to the works without additional knowledge - or whether more complete and updated anthropological references should be provided.